Effects of TiO2 decorated reduced graphene oxide on mechanical and tribological properties of thermosetting polyimide. Issue 9 (2nd September 2022) - Wu, Jianyu; Liu, Hong; Wang, Hongding; Ma, Wei; Wang, Tingmei; Wang, Qihua
ABSTRACT: In this paper, TiO2 decorated reduced graphene oxide nanocomposite (TiO2 @RGO), synthesized with the help of 3-Triethoxysilylpropylamine (APTES), was utilized to reinforce polyimide (PI), and the mechanical and tribological properties of this hybrid reinforced nanocomposite were investigated. Compared with RGO, TiO2, and TiO2 /RGO mixture added to PI, TiO2 @RGO showed synergistic effect and significant enhancement of the compress performance and wear resistance of PI composites. The compressive strength and modulus are increased by about 31% and 43%, respectively, compared to pure PI. Under high-load 300 N, the wear rate of TiO2 @RGO reinforced PI composite decreased to one-tenth of that of pure PI, and was also much lower than other comparatively studied filler reinforced PI composites. In the analysis of the mechanical and friction mechanism, the excellent mechanical and tribological properties of TiO2 @RGO/PI composite are attributed to the 'ball-on-plane' structure of TiO2 @RGO composite and the chemical bonds between RGO and TiO2, which are assumed to stop crack propagation in the friction and lead to the wear reduction of PI composite. The outstanding mechanical and tribological properties of TiO2 @RGO/PI composite show its promising potential of application as the tribological film that high wear resistance is required under heavy load. GRAPHICAL ABSTRACT: uf0001